Biodiesel synthesis from Mesua ferrea oil using waste shell derived carbon catalyst. (June 2018) - Bora, Akash Pratim; Dhawane, Sumit H.; Anupam, Kumar; Halder, Gopinath
Abstract: The present study investigates the feasibility of synthesis of environmentally benign heterogeneous carbonaceous catalyst and biodiesel production from a single source i.e. Mesua ferrea Linn (MFL) seeds. The study primarily focuses on the optimisation of biodiesel synthesis process considering four parameters viz. reaction time, temperature, catalyst loading and methanol to oil ratio (M/O). The parametric influence on the free fatty acid (FFA) conversion has been studied to evaluate the most significant parameters. The contribution factor and analysis of variance results reveal that temperature is the most significant parameter influencing the FFA conversion followed by reaction time and catalyst content. The optimum conditions observed for maximum FFA conversion of 95.57% were: temperature 55 °C, time 2 h, catalyst content 10 wt% and M/O 6:1. The physico-chemical properties of the produced Mesua ferrea oil methyl ester (MFOME) were analysed following ASTM standard methods and found to be within limit; and compatible with the conventional diesel. Thus, the study suggests that the MFL seeds could be a promising source for the synthesis of an effective heterogeneous catalyst; and eco-friendly energy efficient sustainable fuel through the concept of green chemistry by converting waste into valuable commodity towards mitigation of increased energy demand. Highlights: MFL seeds were used as a prominent precursor for catalyst synthesis and oil extraction. Indigenously developed catalyst was highly effective in converting acid oil into biodiesel. The results revealed the optimum conditions for maximizing the FFA conversion. ANOVA study indicated temperature and catalyst loading as most influential parameters. The catalyst showed higher activity to yield biodiesel of compatible standards.